Predictors and outcomes of delayed graft function after living‐donor kidney transplantation. (26th October 2015) - Redfield, Robert R.; Scalea, Joseph R.; Zens, Tiffany J.; Muth, Brenda; Kaufman, Dixon B.; Djamali, Arjang; Astor, Brad C.; Mohamed, Maha
Summary: Delayed graft function (DGF) following deceased donor kidney transplantation is associated with inferior outcomes. Delayed graft function following living‐donor kidney transplantation is less common, but its impact on graft survival unknown. We therefore sought to determine risk factors for DGF following living‐donor kidney transplantation and DGF's effect on living‐donor kidney graft survival. We analyzed living‐donor kidney transplants performed between 2000 and 2014 in the UNOS dataset. A total of 64 024 living‐donor kidney transplant recipients were identified, 3.6% developed DGF. Cold ischemic time, human leukocyte antigen mismatch, donor age, panel reactive antibody, recipient diabetes, donor and recipient body mass index, recipient race and gender, right nephrectomy, open nephrectomy, dialysis status, ABO incompatibility, and previous transplants were independent predictors of DGF in living‐donor kidney transplants. Five‐year graft survival among living‐donor kidney transplant recipients with DGF was significantly lower compared with graft survival in those without DGF (65% and 85%, respectively, P < 0.001). DGF more than doubled the risk of subsequent graft failure (hazard ratio = 2.3, 95% confidence interval: 2.1–2.6; P < 0.001). DGF after living‐donor kidney transplantation is associated with inferior allograft outcomes. Minimizing modifiable risk factors may improve outcomes in living‐donor kidney transplantation.